The Use of Rumen Contents as Bio–Activators for Fermentation in Goat Manure Fertilizer Production - Pancapalaga Wehandaka; Suyatno Suyatno; Sedlacek David (E3S Web of Conferences, 2021)
Slaughterhouse waste cause environmental problems. Rumen content comprise a lot of enzymes of potential bacteria as bio–activators in the process of making goat manure fertilizer. The study aimed to evaluate the quality of goat manure fertilizer added with rumen content. The materials used were goat manure and cattle rumen contents. The research method uses a Completely Randomized Designed (CRD). The percentages of cattle rumen contents treatments i.e. 0 %, 5 %, 10 % and 15 %. The variables measured were Nitrogen (N), Phosphor (P), Potassium (K), Carbon organic, C/N ratio and moisture content. The results showed, the addition of rumen contents had a very significant effect (p < 0.01) on C organic, P, N, and C/N, but had no significant (p > 0.05) on K and moisture content. The results showed that the best treatment was addition of 15 % rumen, that had N 1.59 %, P 0.15 %, K 0.72 %, C organic 30.60 %, C/N 19.24 %, and moisture content 45.86 %. This content had fulfilled SNI 19–7030–2004 for goat manure fertilizer. It could be concluded that giving rumen contents could increase N, P, K, C organic and decrease C/N and moisture content.